Neodymium isotopes as a paleo-water mass tracer: A model-data reassessment. (1st March 2022) - Pöppelmeier, Frerk; Lippold, Jörg; Blaser, Patrick; Gutjahr, Marcus; Frank, Martin; Stocker, Thomas F.
Abstract: Proxy reconstructions from deep ocean sediments have helped to shape our understanding of the role of the global overturning circulation in past climate change. Neodymium (Nd) isotopes have contributed to this knowledge, as a tracer of past bottom water provenance and mixing. Here, we extend the implementation of Nd isotopes in the physical-biogeochemical Bern3D model by revising a number of critical parameterizations, which result in an improved description of the marine Nd cycle. We exploit the dynamically consistent framework of the model, which allows us to assess the processes driving non-conservative Nd isotope behavior with a particular focus on the Last Glacial Maximum (LGM) and its substantially different climatic, oceanic, and biogeochemical boundary conditions. We show that the more radiogenic Nd isotopic compositions found throughout the glacial ocean can be explained by changes in the weathering input fluxes and do not require large reorganizations of the deep circulation. Our findings further highlight that the Nd isotopic composition of a water mass can not only be significantly affected by a benthic Nd flux, but also be modified by the vertical downward transport of Nd via reversible scavenging. While these non-conservative processes only have a limited impact in the modern ocean, they were substantially more pronounced during the LGM and mostly independent of the circulation state, with their contributions being non-linear, partially opposing, and spatially variable. During the transiently simulated deglaciation Nd isotope variations induced by major circulation weakenings and resumptions are found to be most pronounced in the South Atlantic, while they are increasingly muted towards the north. Hence, it emerges that the interpretation of authigenic Nd isotope records requires more spatially specific considerations of non-conservative processes in order to more reliably infer basin-scale ocean circulation and water mass mixing of the past. Highlights: Revised Nd implementation in the Bern3D model improves agreement with observations. Dynamically consistent physical-biogeochemical framework including full Nd cycle. Glacial Nd isotopes globally more radiogenic due to changed weathering input fluxes. εNd behaved less conservatively during the glacial independent of the circulation. Deglacial variability of the circulation best captured by εNd in the South Atlantic.